Role of cytokines in myocardial ischemia and reperfusion - H. S. Sharma; D. K. Das (Hindawi Limited, 1997)
Mediators of myocardial inflammation, predominantly cytokines, have for many years been implicated in the healing processes after infarction. In recent years, however, more attention has been paid to the possibility that the inflammation may result in deleterious complications for myocardial infarction. The proinflammatory cytokines may mediate myocardial dysfunction associated with myocardial infarction, severe congestive heart failure, and sepsis. A growing body of literature suggests that inflammatory mediators could play a crucial role in ischemia-reperfusion injury. Furthermore, ischemia-reperfusion not only results in the local transcriptional and translational upregulation of cytokines but also leads to tissue infiltration by inflammatory cells. These inflammatory cells are a ready source of a variety of cytokines which could be lethal for the cardiomyocytes. At the cellular level it has been shown that hypoxia causes a series of well documented changes in cardiomyocytes that includes loss of contractility, changes in lipid metabolism and subsequent irreversible cell membrane damage leading to cell death. For instance, hypoxic cardiomyocytes produce interleukin-6 (IL-6) which could contribute to the myocardial dysfunction observed in ischemia reperfusion injury. Ischemia followed by reperfusion induces a number of other multi-potent cytokines, such as IL-1, IL-8, tumor necrosis factor-α (TNF-α), transforming growth factor-β1 (TGF-β1) as well as an angiogenic cytokine/ growth factor, vascular endothelial growth factor (VEGF), in the heart. Intrestingly, these multipotent cytokines (e.g. TNF-α) may induce an adaptive cytoprotective response in the reperfused myocardium. In this review, we have included a number of cytokines that may contribute to ventricular dysfunction and/or to the cytoprotective and adaptive changes in the reperfused heart.